English for Informatics: Insights from Evaluating a Contextual Learning Module - Fitra Elia; Devi Sospita; Ria Wuri Andary (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This research article presents the findings of the assessment of the English I Module used by students of the informatics study program. The evaluation's goal is to determine how well the module supports the students' comprehension of technical English associated with the informatics sector in terms of effectiveness, relevance, and applicability. A questionnaire covering topics like material comprehension, content relevance to the workplace, contextual learning approaches, and preferred learning activities was filled out by 27 students and used to gather data. The results show that the module has been successful in promoting learning and has helped students' technical vocabulary and reading skills. These findings provide valuable insights for the development of future English modules that are more culturally relevant and adaptable.